2021
DOI: 10.1186/s12866-021-02411-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of cellulase and ceftazidime, alone and in combination against Pseudomonas aeruginosa biofilms

Abstract: Background Biofilms are a main pathogenicity feature of Pseudomonas aeruginosa and has a significant role in antibiotic resistance and persistent infections in humans. We investigated the in vitro activities of antibiotic ceftazidime and enzyme cellulase, either alone or in combination against biofilms of P. aeruginosa. Results Both ceftazidime and cellulase significantly decreased biofilm formation in all strains in a dose-dependent manner. Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Enzymatic debridement is another option if we can identify appropriate enzymes. Toward this end, glycoside hydrolases (GHs) are effective for the dispersion of some biofilms, most notably commercial cellulase and amylase preparations [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. While encouraging, commercial enzyme preparations appear to be effective at high concentrations, and we have confirmed that their purity is sometimes questionable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic debridement is another option if we can identify appropriate enzymes. Toward this end, glycoside hydrolases (GHs) are effective for the dispersion of some biofilms, most notably commercial cellulase and amylase preparations [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. While encouraging, commercial enzyme preparations appear to be effective at high concentrations, and we have confirmed that their purity is sometimes questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes known as glycoside hydrolases (GHs) have shown promise in degrading the polysaccharides in the EPS to disperse bacteria. Amylase, cellulase, dispersin B, alginate lyase, and other GHs can disperse biofilms both in vitro and in vivo [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Even so, the great diversity of EPS polysaccharides in any single biofilm represents a significant challenge to the therapeutic application of GHs to aid in the clearance of biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm formation was defined compared to the control wells. There were four categories of isolates: non-biofilm producers (OD T < ODc), weak-biofilm producers (ODc < OD T < 2 × ODc), moderate-biofilm producers (2×ODc < OD T < 4 × ODc), and strong-biofilm producers (4 × ODc < OD T ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…2019; Kamali et al . 2021). Previously, our research group confirmed that PA 11 has a strong ability to produce biofilms, so, we chose PA 11 as the representative strain in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…For the reason biofilms-related drug resistance in PA occurred with high frequency, we assayed the inhibition of biofilm formation using crystal violet in 96-well flatbottom polystyrene plates, as previously described with minor modification (Dosler and Karaaslan 2014;Chanda et al 2017;Martinez et al 2019;Vipin et al 2019;Kamali et al 2021). Previously, our research group confirmed that PA11 has a strong ability to produce biofilms, so, we chose PA11 as the representative strain in this experiment.…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%